PENERAPAN PRODUKSI BERSIH PADA INDUSTRI KECIL MENENGAH (IKM) PENGOLAHAN TAHU DI INDONESIA: LITERATUR REVIEW - Nurul Izzah Aulia; Nastiti Siswi Indrasti; Andes Ismayana (Jurnal Teknologi Industri Pertanian, 2023)
The tofu industry, especially small industries, still has a low awareness of the environmental impacts caused by the production process. Reduction of environmental impact and production efficiency in tofu industry activities can be solved by applying cleaner production. This study aims to examine the applications of cleaner production in tofu processing SMEs in Indonesia. The method used is an exploratory approach to review the contents of several articles from national and international journals. Reviews on articles can be in the form of identification of the tofu processing, problems, CP reccomendations, results of technical, financial and environmental analysis and the priorities for cleaner production. CP opportunities that can be recommended for tofu processing SMEs in Indonesia are 1) The washing process in stages, 2) Making water recycling installations, 3) Making additional funnels on the milling machine, 4) Making energy-saving stoves, 5) Substitution of firewood with coconut shells, 6) Utilization of tofu dregs for animal feed, 7) Making Nata de Soya from whey, 8) Good Manufacturing Practice (GMP) application. Keywords: cleaner production, small and medium industry, tofu industri